Healthy Gymnastics Training as an Effort to Improve the Fitness and Immunity of MIT-SAQU Dar-El Iman Students: Pelatihan Senam Sehat sebagai Upaya Meningkatkan Kebugaran dan Imunitas Murid MIT SAQU Dar El Iman - Sri Handayani; Fitri, Wiya Elsa; Angelia, Inge (Universitas Lancang Kuning, 2024)
The MIT-SAQU Dar-El-Iman school has never received a visit and monitoring from the local health center, so there are still students who seem not to comply with the health protocol. The activity is carried out in 2 stages, the first is to conduct gymnastic training for teachers with the aim that this exercise can still be used later. second, conducting gymnastic training for students, to create students' enjoyment in doing gymnastics which indirectly increases their knowledge about COVID-19 from the lyrics of gymnastic songs and improves student fitness after doing gymnastics. Activities are carried out on Saturday, 13 and 20 January 2022, 08:00 – 12:00 WIB in the field. As a result of this activity, 6 students were appointed as healthy gymnastics cadres, there was an increase in students' knowledge about healthy gymnastics to increase body immunity and concentration and healthy gymnastic activities began to be routinely carried out in schools after being given counseling. Implementation of this activity is very important in cultivating fitness which can increase student immunity so that it is not easy to contract disease.